Towards Mixed-Initiative Access Control - Dewan, Prasun; Grudin, Jonathan; Horvitz, Eric (CollaborateCom, 2007)
The difficult task of providing access to shared objects is, typically, carried out individually by access authorizers. Using a presence-based “thought experiment” and an abstract architecture, we motivate and explain here the idea of using distributed collaborative environments to perform this activity. In these environments, the initiative in distributing access rights to shared objects can be taken by information guardians, information consumers, and tools that act as agents of the guardians and consumers. Information consumers are responsible for sending access requests to information guardians; their agents (partially or completely) automate this task for them. Information guardians are responsible for authorizing accesses; their agents automate this task for them.